Social mobility and gender: An analysis by federative entity - Campos-Vazquez, Raymundo M.; Gutiérrez Dorantes, José Daniel (Estudios Económicos de El Colegio de México, 2024)
This work studies social mobility by gender at the regional and state level in Mexico. Two surveys designed to measure social mobility in Mexico are used, the 2016 Module of Intergenerational Social Mobility (Módulo de Movilidad Social Intergeneracional) and the 2017 ESRU Social Mobility Survey (Encuesta ESRU de Movilidad Social). An index of socioeconomic status is constructed both for the current household (children) and the household of origin (parents) based on retrospective questions from when the respondent was 14 years old. Using rank-rank regressions, we find that at the national level, women have lower intergenerational persistence and lower expected rank than men. At the regional and state level, those results are not so statistically clear. In the lower end of the socioeconomic distribution, expected ranks are approximately the same across states; however, at the upper end, it is observed that men have higher expected ranks than women in 13 states.